Application of a new constitutive model to the analysis of plate load tests in a pyroclastic rock. (September 2015) - Amorosi, Angelo; Aversa, Stefano; Boldini, Daniela; Laera, Anita; Valerio Nicotera, Marco
Abstract: This paper deals with a new critical state-based constitutive model for soft rocks and with its application to the analysis of the response of a pyroclastic rock during in situ plate load tests. The model, formulated in the single-surface plasticity framework, is characterised by the following main features: (i) a generalised three-invariant yield surface capable of reproducing a wide set of well-known criteria, (ii) the dependency of the elastic stiffness on the current stress state by means of a hyperelastic formulation and (iii) the ability of simulating the plastic strain driven structure degradation processes by a set of appropriate isotropic hardening laws. The constitutive model was implemented in a commercial Finite Element code by means of an explicit modified Euler scheme with automatic sub-stepping and error control. The procedure does not require any form of stress correction to prevent drift from the yield surface. The model was applied to simulate the response of a pyroclastic rock, the Neapolitan Yellow Tuff, to in-situ plate load tests conducted by 500 mm and 300 mm circular plates. In particular, in each location a first test was carried out adopting the large plate, applying a loading and unloading cycle; this was followed by a second loading stage performed on the same portion of rock by the smaller plate up to larger stress levels. Test results pointed out some specific features of the rock response under such loading conditions, including non-linear elastic behaviour and structure degradation, this latter highlighted by the overall reduction of the shear strength parameters. The numerical analyses showed a fairly good agreement with the in-situ experimental data, substantiating the relevance of the selected constitutive assumptions for the soft rock under investigation. Highlights: This paper deals with a new critical state-based constitutive model for soft rock. The model accounts for non-linear elastic behaviour and structure degradation. The response of a pyroclastic rock during in situ plate load tests is analysed. The numerical analyses show a fairly good agreement with the in-situ experimental data. The evolution of different internal variables is provided.